2002
DOI: 10.1093/ortho/29.3.197
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of teenagers’ decisions to undergo orthodontic treatment with fixed appliance

Abstract: Motivation for the decision to undergo orthodontic treatment seemed to be social norms, and the beauty culture in their reference group and in society in general. The teenagers were not fully conscious of these external influences. Their opinion, as a group, was that they had made an independent decision to undergo orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 12 publications
5
71
2
6
Order By: Relevance
“…This probably happens because both patients and caregivers overestimate the perceived need for orthodontic treatment in the hope of receiving such a treatment (3), in addition to the fact that orthodontic appliances have been associated with status or social trends (16). Also, society and media reinforce facial stereotypes on a daily basis, thus creating social patterns and beauty values which serve as important external factors in promoting the interest in orthodontic treatment (14,24).…”
Section: Discussionmentioning
confidence: 99%
“…This probably happens because both patients and caregivers overestimate the perceived need for orthodontic treatment in the hope of receiving such a treatment (3), in addition to the fact that orthodontic appliances have been associated with status or social trends (16). Also, society and media reinforce facial stereotypes on a daily basis, thus creating social patterns and beauty values which serve as important external factors in promoting the interest in orthodontic treatment (14,24).…”
Section: Discussionmentioning
confidence: 99%
“…Several well-designed studies, using qualitative research methods have confirmed that young people with malocclusion, who seek orthodontic treatment, are dissatisfied with and have a sense of shame about the appearance of their teeth. [44][45][46] This perceived feeling of being unattractive and different to other people is made worse by the expression of supposed societal norms, through peer group pressure and images in the media. The awkwardness that young people feel about the appearance of their teeth leads to various coping strategies in social situations, including not showing their teeth when they smile, avoiding having their photograph taken and embarrassment when their photographs are shared through social media.…”
Section: Social Well-beingmentioning
confidence: 99%
“…Assessment of social media content plays an important role in understanding the motivation factors, expectations, and experiences of orthodontic patients. 11 In the literature, there are a limited number of studies examining the relationship between social media and orthodontics. However, there are no studies investigating the information about lingual orthodontic treatment through social media.…”
Section: Introductionmentioning
confidence: 99%